CHARACTERISTIC OF INTERACTION STIMULANT FACTORS ANALYSIS ON SOCIAL MEDIA INSTAGRAM ACCOUNT @DITJENPAJAKRI - Roro Wuri Arenggoasih; Ifadatul Khatibah (IAIN Salatiga, 2019)
Consciously or not, the social media era has moved the flow of information to their gadgets. Indonesia has been ranked third as an active user of social media Instagram. So, currently both personally and institutionally it is not unusual to have an Instagram account such as the Republic of Indonesia Directorate General of Tax with account @ditjenpajakri. Exactly, the beneficiary of the account has become an interactive medium that increases popularity to encourage trust and conversion tax in Indonesia towards the tax-aware generation. Therefore, the purpose of this study is to determine the characteristics of interaction stimulant factors on the @ditjenpajakri account with the content analysis method on various components that encourage interaction in 504 posts in 2018. The results of the research reveal that the booster component of the @ditjenpajakri account interaction consists of the type of photo/image, the number of likes/love and followers/comments, types of captions, and hashtag.